Poly-ε-caprolactone based nanoparticles for delivery of genistein in melanoma treatment - Juliana Palma Abriata; Marcela Tavares Luiz; Juliana Santos Rosa Viegas; Fernando Fumagalli; Shaiani Maria Gilde Melo; Flavio da Silva Emery; Juliana Maldonado Marchetti; Fabiana Testa Moura de Carvalho Vicentini (Universidade de São Paulo, 2024)
Abstract We developed poly-ε-caprolactone (PCL)-based nanoparticles containing D-α-tocopherol polyethylene glycol-1000 succinate (TPGS) or Poloxamer 407 as stabilizers to efficiently encapsulate genistein (GN). Two formulations, referred to as PNTPGS and PNPol, were prepared using nanoprecipitation. They were characterized by size and PDI distribution, zeta potential, nanoparticle tracking analysis (NTA), GN association (AE%), infrared spectroscopy (FT-IR), and differential scanning calorimetry (DSC). PNTPGS-GN exhibited a particle size of 141.2 nm, a PDI of 0.189, a zeta potential of -32.9 mV, and an AE% of 77.95%. PNPol-GN had a size of 146.3 nm, a better PDI than PNTPGS-GN (0.150), a less negative zeta potential (-21.0 mV), and an AE% of 68.73%. Thermal and spectrometric analyses indicated that no new compounds were formed, and there was no incompatibility detected in the formulations. Cellular studies revealed that Poloxamer 407 conferred less toxicity to PCL nanoparticles. However, the percentage of uptake decreased compared to the use of TPGS, which exhibited almost 80% cellular uptake. This study contributes to the investigation of stabilizers capable of conferring stability to PCL nanoparticles efficiently encapsulating GN. Thus, the PCL nanoparticle proposed here is an innovative nanomedicine for melanoma therapy and represents a strong candidate for specific pre-clinical and in vivo studies.